Internal Control Practices and Financial Performance of Listed Commercial Banks in Nigeria - Tamunoemi Bruce Longjohn; Promise Wokeh I. (International Journal on Economics, Finance and Sustainable Development, 2022)
This paper studied internal control practices and financial performance of listed commercial banks in Nigeria. The scope of this study is limited to listed commercial banks. In the organized sector of the economy which is the private sector. A hypothesis was made to guide this study. The study employed cross-sectional survey design approaches, comprising descriptive and exploratory research designs. The targeted population of this study comprises all the 13 listed commercial banks in Nigeria. Both primary and secondary data was used in this study, five hundred (500) questionnaire was administered to management staff of the banks. Findings from pooled correlation test of hypothesis one shows that internal control practices is positively and significantly correlated with commercial banks financial performance. The empirical tests conducted revealed that internal control practices have significant relationship with financial performance of listed commercial bank in Nigeria. This therefore suggests that an optimal internal control practices affects the institutions positively, while a wrong mixture inadequate internal control and fraud prevention measures affects institution's profitability adversely.